Is it time to move toward freeze-all strategy? - A retrospective study comparing live birth rates between fresh and first frozen blastocyst transfer - Reeta Biliangady; Rubina Pandit; Nutan Kumari Tudu; Poornima Kinila; Uma Maheswari; Indu S. T Gopal; Ambika G Swamy (Wolters Kluwer Medknow Publications, 2019)
Background: Cryopreservation of all embryos followed by transfer in subsequent cycles has emerged as an effective alternative to fresh embryo transfer (ET) in order to overcome the negative effect of superovulation on endometrial receptivity. Aims: The aim of this study was to compare the reproductive outcomes between fresh ET and first frozen ET (FET) from "freeze-all" group of embryos. Setting: This study was conducted at a private in vitro fertilization center. Design: This was a retrospective study. Patients and Methods: A total of 503 patients fulfilling the inclusion criteria between 2012 and 2017 were included. Of 503, 386 patients underwent fresh ET and 117 patients underwent FET following cryopreservation of all embryos. The results of only first FET were considered to eliminate the confounding factor of poor-quality embryos in subsequent transfer. Results: FET resulted in statistically significant higher live birth rate (44.44% vs. 33.41%), implantation rate (45.08% vs. 30.22%), and clinical pregnancy rate (57.26% vs. 38.6%) compared to fresh ETs. No difference was observed in the abortion rate between the two groups. Conclusion: Reproductive outcomes were significantly better in the freeze-all group compared to fresh ET suggesting that the altered hormone levels during controlled ovarian stimulation could mediate an asynchrony between the endometrium and the transferred embryos, leading to implantation failure.